2002
DOI: 10.1113/eph8702391
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Infusion Attenuates Muscle Fatigue in Rat Plantaris Muscle During Prolonged Indirect Stimulation in Situ

Abstract: showed that ingestion of a glucose polymer (1.8 g min _1 ) increased exercise time from 192 to 252 min during cycling at 70 % of the maximum rate of oxygen uptake (◊J ,max ). In the study by McConell et al. (1999) exercise time at 69 % ◊J ,max increased from 152 to 199 min with ingestion of 287 g CHO. This phenomenon has also been described in animals (Dill et al. 1932; Bagby et al. 1978; Slentz et al. 1990). For instance, in the study by Slentz et al. (1990) running time to exhaustion, at 8 % gradient and 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
25
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 14 publications
9
25
0
Order By: Relevance
“…We have shown that glucose infusion attenuated muscle fatigue in the rat plantaris muscle stimulated indirectly for 60 min in situ (Karelis et al 2002). This was not associated with any reduction in muscle glycogen utilization, which is consistent with data from Tsintzas et al (1995Tsintzas et al ( , 1996Tsintzas et al ( , 2001 since the plantaris muscle is predominantly composed of type II fibres (Delp and Duan 1996).…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…We have shown that glucose infusion attenuated muscle fatigue in the rat plantaris muscle stimulated indirectly for 60 min in situ (Karelis et al 2002). This was not associated with any reduction in muscle glycogen utilization, which is consistent with data from Tsintzas et al (1995Tsintzas et al ( , 1996Tsintzas et al ( , 2001 since the plantaris muscle is predominantly composed of type II fibres (Delp and Duan 1996).…”
Section: Introductionsupporting
confidence: 82%
“…The beneficial effect of glucose infusion on dynamic force during prolonged indirect stimulation, however, was not associated with any improvement in twitch force. Karelis et al (2002) also reported a beneficial effect of glucose infusion on dynamic force in the rat plantaris muscle indirectly stimulated in situ. However, when saline was infused the reduction in dynamic force was larger (70%) than that seen in the current experiment (45%).…”
Section: Discussionmentioning
confidence: 94%
“…It also raises the possibility that the hypoglycemia experienced by the LG animals during exercise may have induced some degree of peripheral fatigue during treadmill exercise. However, in the Karelis et al [24] study, plasma glucose levels were very high during infusion, nearly twice the initial and control levels and, in the control condition, there was no decline in blood glucose. Further, the slight hypoglycemia experience by the LG animals during stimulation (present study) was not associated with alterations in force or fatigue.…”
Section: Discussionmentioning
confidence: 80%
“…It should be pointed out that Karelis et al [24] showed that glucose infusion during in situ stimulation attenuated the extent of fatigue and partially restored force in fatigued muscle, possibly by maintaining Na/K pump function. is suggests that blood glucose may have a direct effect on muscle function during fatiguing exercise.…”
Section: Discussionmentioning
confidence: 99%
“…In these experiments we observed that, before exercise, rats treated with CMP/UMP had significantly higher muscle glucose concentrations compared to nontreated rats. A possible explanation is that rats treated with CMP/UMP undergoes an adaptation state, which allows them to store higher levels of glucose in muscle, and can, therefore, endure more exercise (21,28). One way of favoring the entry of glucose in the cells is up regulating the glucose transporters present in the cell membrane such as the GLUT family (22).…”
Section: Discussionmentioning
confidence: 99%